COVID-19 Related Practices in a Remote Rural Municipality of Nepal – an Observational Study - Jha, Jay Prakash; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Health promotion, specific preventive measures, disease screening and timely isolation are the mainstay for controlling the spread of COVID-19 infection. This study is conducted in a remote place of Nepal to describe the various preventive measures practised by the community for COVID prevention and general health fitness. Methods: An observational study was conducted in Guthichaur Rural Municipality (RM) of Jumla. The subjects were tested for antigens by Rapid Diagnostic Test (RDT) kit for COVID-19 infection. Subjects were evaluated with a questionnaire to assess the awareness and practices related to COVID prevention and health promotion, including Yogasan and Pranayam. Data were analyzed by descriptive (mean and standard deviation) and inferential (Chi-Square test) statistics. Results: A total of 546 subjects were tested for COVID, 49 were positive by RDT (case positivity rate 9%). Among them, 218 were evaluated by questionnaire. The mean age was 40.39 years (range 5 – 81). The sex ratio was 1.9, favouring males; but females were more (58%) among COVID positive. Common complaints were headache (39.4%), fever (33.3%), dry cough (24.2%) and body ache (24.2%). There were significantly higher positive subjects who had contact with COVID-19 positive individuals within the past 14 days (p<0.001). Most of the subjects in both groups practised standard preventive measures. Hot water and herbal products were commonly used in the community. The awareness and practices of Yogasan and Pranayam were low in all subjects, but more COVID positive subjects were unaware than COVID negative ones. Conclusion: Most individuals in the community practised general preventive measures, but their awareness and practice of Yogasan and Pranayam were poor. Women should be encouraged to the screening test. More awareness about health fitness should be given in the community, and the COVID management system needs to be improved.